How the blockchain technology can - johansson, Jonas; Nilsson, Christoffer (My University, 2018)
Today, sustainability is considered as a high priority and it is on the management agenda for major corporations. It has experienced an increase in customer demand, pressuring corporations to act in a more sustainable way to stay relevant and competitive. One industry that is experiencing an increased request to act sustainable is the construction industry. The construction industry differs quite a lot from other industries since it is project based and built on temporary relationships. Subcontractors are temporarily engaged in the projects, often by a main contractor, to perform tasks which they are specialized in. The subcontractors additionally engage their own respective subcontractors. This makes it harder to control and ensure that all involved actors are acting in a sustainable way due to the multiple tiers of contractors and complex nature of the projects. A technology that recently has gotten a lot of attention is the blockchain technology. It can be described as a shared, distributed ledger technology, which was created as an enabler for the cryptocurrency Bitcoin. The technology has, in the recent years, been widely discussed as a potential business enhancer. It can for example provide immutable record-keeping; enables the usage of smart contracts; and enhance transparency within the network. The blockchain technology has the potential to disrupt current business practices and decrease the required amounts of trust needed in business relationships. Because of the increasing demand of sustainability practice within the construction industry, technologies that can enhance it becomes of interest for further investigation. Therefore, this thesis has been investigating if the blockchain technology can enhance sustainability for contractors within the construction industry. To achieve the purpose, data has been gathered from literature, interviews as well as benchmarking of existing blockchain solutions in business. The empirical gatherings resulted in identifying seven issues related to sustainability within the construction industry, and relevant information regarding blockchain that is not mentioned in the literature. The issues found in the empirical data were analysed by a framework which consist of three blocks. The first one concerns whether the issues found are within the scope of sustainability. The second block concludes, using a proposed blockchain decision tree, if the issues have a potential blockchain solution. The final block is a SWOT analysis, where the blockchain solution for each issue is evaluated in isolation. The issues of non-sustainable material used by the contractor, undeclared work, accidents, employee payment and limited contractor base where concluded to potentially be prevented, or mitigated, with a blockchain solution. It is, however, still a immature technology that needs to be further developed and understood in order to bring out its true potential. Several of these issues can be prevented, or mitigated, by the same kind of blockchain setup, which makes it to a more profitable alternative than separately evaluating them.
Keywords: Samhällsbyggnadsteknik; Civil Engineering